1977
DOI: 10.1039/f19777300632
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenation of acetylene in excess ethylene on an alumina supported palladium catalyst in a static system

Abstract: Studies have been made of the kinetics of the hydrogenation of mixtures containing 2 % of acetylene in ethylene on an alumina supported palladium catalyst in a static system. Information ' A. Farkas and L. Farkas,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(37 citation statements)
references
References 0 publications
1
36
0
Order By: Relevance
“…and also explains the reaction orders obtained in agreement with the general opinion that hydrogen adsorbes dissociatively in this type of reactions (27,28,29). …”
Section: D(f:)_d~jsupporting
confidence: 90%
“…and also explains the reaction orders obtained in agreement with the general opinion that hydrogen adsorbes dissociatively in this type of reactions (27,28,29). …”
Section: D(f:)_d~jsupporting
confidence: 90%
“…These values are lower than the effective pore diffusivities measured by Asplund [57] for acetylene hydrogenation catalysts in the form of pellets and crushed pellets of larger particle size than those employed here. Furthermore, a 5-point Arrhenius plot (323-373 K) used to calculate apparent activation energy for acetylene conversion up to 99.5% (R 2 = 0.986) give a value of 47.3 kJ mol À1 (for 50-CuPd) similar to the value (46.8 kJ mol À1 ) reported by McGowan et al [58]. Values of 40 kJ mol À1 [59] and between 40 and 50 kJ mol À1 [60] have been reported for acetylene hydrogenation to ethylene under conditions which have been tested and confirmed to be representative of reaction in the absence of transfer resistances.…”
Section: Resultsmentioning
confidence: 82%
“…The selective behaviour of the acetylene hydrogenation reaction is based upon the existence of two separate types of reaction sites, as first proposed by McGown et al (1977). This theory has been gaining acceptance during recent years and has been confirmed by various other researchers (AI-Ammar and Webb, 1978; Moses et al 1984).…”
Section: Reaction Imentioning
confidence: 78%
“…Typical inlet and outlet compositions for a tail end acetylene reactor have reported by a variety of researchers (Battiston et al, 1983;McGown et al, 1977; Moses et al, 1984) and are shown in Table 1 . These values will be used in THE CANADIAN JOURNAL OF CHEMICAL ENGINEERING, VOLUME 69, FEBRUARY, 1991 the modelling and simulation of the hydrogenation process.…”
Section: Acetylene Reactor Configurationmentioning
confidence: 99%
See 1 more Smart Citation